Activity-based costing (ABC) in SMEs and innovative initiatives: possible option or expired? - Escobar-Mamani, Fortunato (2021)
The quantification of production/service costs to determine the market price is fundamental in offering the maximum value of satisfaction. Therefore, management accounting is essential. One of the alternative tools is activity-based costing, known as ABC system, an alternative method to overcome the limitations of traditional indirect cost systems, which somehow distort the actual accounting of costs. Will exploring its development, applicability, challenges and benefits still be a possible option? This study aimed at reviewing the scientific literature produced on the activity-based costing system in recent years, identifying trends of adoption and challegnes of implementation in various manufacturing and service firms. High impact journals indexed in PubMed, Web of Science (WoS), Scopus, among others, were analyzed. The results show an increase of publications on the implementation of the ABC system in PubMed (855 publications), WoS (1131) and Scopus (2535). The results show that its applicability remains a possible option as an alternative costing tool for SME managers or owners. This study concludes that the application of the ABC system is adequate to determine real costs and could guarantee more reasonable and competitive prices in the market. However, there is still resistance to its implementation due to human and technological ignorance.